Evaluation of CRISPR/Cas9 exon‐skipping vector for choroideremia using human induced pluripotent stem cell‐derived RPE. (4th December 2022) - Iwagawa, Toshiro; Masumoto, Hiroki; Tabuchi, Hitoshi; Tani, Kenzaburo; Conklin, Bruce R.; Watanabe, Sumiko
Abstract: Background: Exon‐skipping is a powerful genetic tool, especially when delivering genes using an AAV‐mediated full‐length gene supplementation strategy is difficult owing to large length of genes. Here, we used engineered human induced pluripotent stem cells and artificial intelligence to evaluate clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR associated protein 9‐based exon‐skipping vectors targeting genes of the retinal pigment epithelium (RPE). The model system was choroideremia; this is an X‐linked inherited retinal disease caused by mutation of the CHM gene. Methods: We explored whether artificial intelligence detected differentiation of human OTX2, PAX6 and MITF (hOPM) cells, in which OTX2, PAX6 and MITF expression was induced by doxycycline treatment, into RPE. Plasmid encoding CHM exon‐skipping modules targeting the splice donor sites of exons 6 were constructed. A clonal hOPM cell line with a frameshift mutation in exon 6 was generated and differentiated into RPE. CHM exon 6‐skipping was induced, and the effects of skipping on phagocytic activity, cell death and prenylation of Rab small GTPase (RAB) were evaluated using flow cytometry, an in vitro prenylation assay and western blotting. Results: Artificial intelligence‐based evaluation of RPE differentiation was successful. Retinal pigment epithelium cells with a frameshift mutation in exon 6 showed increased cell death, reduced phagocytic activity and increased cytosolic unprenylated RABs only when oxidative stress was in play. The latter two phenotypes were partially rescued by exon 6‐skipping of CHM . Conclusions: CHM exon 6‐skipping contributed to RPE phagocytosis probably by increasing RAB38 prenylation under oxidative stress. Abstract : RPE cells derived from hiPSCs with a frameshift mutation in exon 6 of CHM showed reduced phagocytic activity under oxidative stress. The phenotype was partially rescued by exon 6‐skipping induced by the CRISPR/Cas9 system.